2020
DOI: 10.3390/f11050570
|View full text |Cite
|
Sign up to set email alerts
|

Localized and Moderate Phosphorus Application Improves Plant Growth and Phosphorus Accumulation in Rosa multiflora Thunb. ex Murr. via Efficient Root System Development

Abstract: Roots have high plasticity with the ability to adapt to heterogeneous nutrient distribution, but little is known about the effects of phosphorus (P) supply methods and levels on Rosa multiflora Thunb. ex Murr. root growth and nutrient accumulation. A pot study was conducted with two P supply methods (mixed and localized application) and three levels (P-deficient, P-moderate and P-adequate). The results showed that with localized application, P-deficient and P-moderate treatments significantly improved total ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Lyu et al ( 2016 ) showed that at the root soil interface, available P could be enhanced by altering the root morphology. Moreover, P has been shown to stimulate root development and subsequent P uptake (Ma et al, 2020 ). In addition, P availability can profoundly influence the plant responses to AM colonization (Campos et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lyu et al ( 2016 ) showed that at the root soil interface, available P could be enhanced by altering the root morphology. Moreover, P has been shown to stimulate root development and subsequent P uptake (Ma et al, 2020 ). In addition, P availability can profoundly influence the plant responses to AM colonization (Campos et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of soybean germplasm revealed moderate to higher values of heritability for most of the root and shoot traits [44,45]. Traits such as the TRL, TSA, TRV, TRT, RDW, and SDW contributed most to the genetic diversity and significantly correlated with P accumulation under SP and LP conditions [46,47]. This result was similar to the results of previous studies, which revealed that the traits TRL, TSA, RDW, and SDW are the major traits for selection of genotypes in maize under different stress conditions [36,42].…”
Section: Discussionmentioning
confidence: 99%
“…All roots were scanned by a scanner (Epson Perfection V700 Photo, Epson America, Inc., Long Beach, CA, USA) at a resolution of 400 dpi. Root images were analysed using WinRhizo Pro 2009b software (Regent Instruments Inc., Québec, QC, Canada) to calculate root length and surface area [15]. We classified root branch order according to Pregitzer's method, where the most distal roots were classified as first-order laterals [19].…”
Section: Measurements Of Root Growthmentioning
confidence: 99%
“…Dried plant samples were digested in a mixture of 5 mL concentrated H 2 SO 4 and 5 mL H 2 O 2 (30%, v/v, qualified as chemically pure) [15]. In the digests, we measured P using the molybdo-vanadophosphate method, and K using the flame spectrophotometry method [22].…”
Section: Measurement Of P and K Accumulationmentioning
confidence: 99%
See 1 more Smart Citation